A traveler of your memories: reflections on the Uses of Interviews in Women’s History (Tempo e Argumento, 2021)
In this paper, I endeavor to explain certain aspects I consider relevant for thinking about a history with oral sources. For this, I will use a set of studies that have contributed to consolidate the scaffolding of the so-called oral history under light of the conceptual contributions of feminist and gender theories and reflections linked to the class problematic. I will focus on one dimension of the concept of citizenship: to vote, in the social construction of women who voted in Argentina in 1951.